Une Femme A Abattre . Kill the Messenger - Verboud, Mathieu; Viallet, Jean-Robert (Nahon, Bruhno, 2006)
Verzio FF submission Out of love for her newly-adopted country, Sibel Edmonds agreed to join the FBI as a translator in the wake of 9/11. But her world gets turned upside-down when Subel reports wrongdoings to her supervisors: one of her colleagues from the Translation Unit is secretly working for the same Turkish officials who are "targetted" by the top-secret FBI investigations that Sibel is working on. As a "reward" for her whistle-blowing, Sibel is fired from the FBI. Today, she is fighting for the very ideals that American democracy relies on, and is facing some of the most wreckless and powerful officials in the U.S. government. Sibel has granted a film crew full and exclusive access to document her story, and her struggle, as we zero in on her secret.